Immunomodulatory role of gut microbial metabolites: mechanistic insights and therapeutic frontiers - Zeng, Li; Qian, Yuwei; Cui, Xiaoyan; Zhao, Jingying; Ning, Zhijun; Cha, Jinglong; Wang, Kun; Ge, Changrong; Jia, Junjing; Dou, Tengfei; Chen, Hongyan; Liu, Lixian; et al. (Frontiers in Microbiology, 2025)
The gut microbiota modulates host immunity through a wide array of metabolic products that function as signaling molecules, thereby linking microbial activity with both mucosal and systemic immune responses. Notably, short-chain fatty acids, secondary bile acids, tryptophan-derived indoles, polyamines, and lipid derivatives play pivotal roles in regulating innate and adaptive immune functions via G protein-coupled receptors, nuclear receptors, and epigenetic pathways. These metabolites modulate immune cell differentiation, epithelial barrier integrity, and the resolution of inflammation in a dose- and site-specific manner. Recent advancements in spatial metabolomics, synthetic biology, and nanomedicine have facilitated the spatiotemporal delivery of these immunomodulatory compounds, revealing novel therapeutic avenues for the treatment of inflammatory and autoimmune disorders. This review summarizes the biosynthesis and immunoregulatory functions of key microbial metabolites, highlights the compartmentalized and systemic mechanisms of action, and discusses emerging therapeutic approaches, including postbiotics, engineered probiotics, and receptor-targeting drugs. We also explore the challenges in achieving personalized microbiome-immune modulation and propose future directions integrating multiomics and AI-driven predictive modeling. Understanding the metabolite-immune axis paves the way for novel interventions targeting host-microbe symbiosis.